2014
DOI: 10.1155/2014/490512
|View full text |Cite
|
Sign up to set email alerts
|

Thai Massage, and Thai Herbal Compress versus Oral Ibuprofen in Symptomatic Treatment of Osteoarthritis of the Knee: A Randomized Controlled Trial

Abstract: The aim of this study was to verify the clinical responses to Thai massage (TM) and Thai herbal compression (THC) for treating osteoarthritis (OA) of the knee in comparison to oral ibuprofen. This study was a randomized, evaluator-blind, controlled trial. Sixty patients with OA of the knee were randomly assigned to receive either a one-hour session of TM or THC (three times weekly) or oral ibuprofen (three times daily). The duration of treatment was three weeks. The clinical assessments included visual analog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 66 publications
(64 reference statements)
2
30
0
Order By: Relevance
“…The obtained results revealed that life expectancy was significantly related to social support and its dimensions. This finding was consistent with the results of Shakerinia [3] and Souliotis et al (2016). Our results regarding the significant negative relationship between cognitive concern subscale (i.e.…”
Section: Resultssupporting
confidence: 94%
“…The obtained results revealed that life expectancy was significantly related to social support and its dimensions. This finding was consistent with the results of Shakerinia [3] and Souliotis et al (2016). Our results regarding the significant negative relationship between cognitive concern subscale (i.e.…”
Section: Resultssupporting
confidence: 94%
“…Rumination, worry, and anxious arousal were significantly different in the elderlies with poor and healthy sleep quality. The obtained data suggested rumination and worry could predict sleep quality, which is consistent with previous studies [5][6][7]. Negative cognitive activities majorly affect sleep quality and its associated problems.…”
Section: Resultssupporting
confidence: 91%
“…The indications of herbal compress used in these studies were pain reduction [ 10 – 19 ] and induction of lactation [ 20 – 22 ]. For studies that investigated the effects of Thai herbal compress on pain reduction, five studies [ 11 , 14 , 15 , 18 , 19 ] were conducted in patients with knee OA, two studies each were conducted in patients with muscle pain [ 16 , 17 ] and labor pain [ 12 , 13 ], and one study [ 10 ] was undertaken in patients with knee OA and patients with muscle pain ( Table 1 ). The majority of the included studies, 11 out of 13, used a quasi-experiment approach [ 10 , 12 – 15 , 17 – 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the included studies, 11 out of 13, used a quasi-experiment approach [ 10 , 12 – 15 , 17 – 22 ]. The remaining studies were randomized controlled trial [ 11 ] and crossover trial [ 16 ]. All 13 studies were conducted in Thailand.…”
Section: Resultsmentioning
confidence: 99%